Kontribusi Pendidikan Agama terhadap Pendidikan Multikultural, Pendidikan Kewarganegaraan, dan Pendidikan Karakter Bangsa: Studi terhadap Ideologi Pendidikan Islam di Indonesia - Abdullah, Mukhammad (Didaktika Religia, 2015)
Plurality of ethnicities, religions, and cultures is Indonesian historical facts. Diversity can be a gift or a disaster. If properly managed it can enrich human lives; on the contrary, if not properly managed it can lead to disaster in the form of tension, conflict, and violence. The function Islamic Education as a subject that is still preserved in the National Education System is expected to shape the character of students, so that they become Muslims who fear (in the sense of obedience to Allah),and at the same time be a citizen of Indonesia that is tolerant, accepting the condition of multi-cultural, and reject all forms of oppression that degrades human dignity. It specifically can be seen from learning objectives, that is to realize the Indonesian people who are religious, noble, knowledgeable, diligent to worship, intelligent, productive, honest, fair, ethical, disciplined, tolerant (tasamuh), maintaining harmony and developing religious culture at school. Philosophically, Islamic education is relevant to and an integral part of the national education system. The position of Islamic education as a subsystem of national education serves not only as a supplement, but as a substantial component. It means that Islamic education is a crucial component of national educational journey. Since the government has proposed the concept of multicultural education, civic education, and character education, then it cannot get rid of Islamic education.